Gender differences in Policing, judicial and penal process of juvenile offenders. - Silva, Alexander Jan Umbrete; Tugahan, Mary Laurence Garibay (2007.)
The study is done in order to determine the gender differences in the treatments of juvenile offenders in Iloilo City in policing, judicial and penal processes. The study focused on detention in the policing process, the dismissal of cases in the judicial process and the rehabilitation of youth offenders in the penal process. The objectives of this study are: (1) to determine the procedures in handling juvenile offenders under the Philippine Judicial System, (2) to identify the different institutions or agencies involved in handling offenders, (3) to determine that male juvenile offenders are subjected to more stringent treatments than female juvenile offenders and (4) to determine that male juvenile delinquents are subject to more stringent treatments than female juvenile delinquents. This is a descriptive-analytical study that made use of key informant interviews. Officers and staff of PNP-Women and Children's Desk, DSWD Field Office VI, BJMP, judge and clerks from Branch 27 of Iloilo Family Courts, Regional Rehabilitation Center for the Youth (RRCY), and A Home for Girls were the participants in the key informant interviews. The study made use of key informant interviews to exact views from different agencies and institutions of the government which handles CICL in Iloilo City. The officers, personnel and staff of these institutions and agencies are personally involved in administering the treatment for CICL. Descriptive method and techniques for dat analysis were employed in describing qualitative results., There are gender differences in the actual treatment, facilities and services in the handling of CICL in the policing and penal processes. There are different and separate facilities for the detention of youth offenders as well as separate institutions for their rehabilitation. However, since there is no facility for detention of females CICL and due to lack of funds and space; they are being detained in jail together with adult female inmates. Female CICL are rehabilitated in A Home for Girls which is not specifically designed for female CICL instead for victims of sexual abuse. There issues and concerns which confront the institutions/agencies within the juvenile justice system as well as regarding the new Republic Act 9344 or the Juvenile Justice and Welfare Act of 2006. In view of the findings of this study, recommendations of the researchers include; with the passing of the Iloilo City Gender Development Code (GAD), the problem of lack of facility girl CICLs has to be addressed by the Iloilo City LGU, address the needs of female youth offenders in detention, rehabilitation and the judicial process, intensify community-based programs and diversion programs, the main responsibility of providing these services to CICL rests to LGUs or MSWD office and the function of DSWD as a national agency is to provide them (LGUs) technical assistance and resource augmentation in relation to the rehabilitation of CICL. Further studies are regarding the perceptions and attitudes of the public towards juvenile delinquency and the different approaches towards treatment, an evaluative or assessment study of Republic Act 9344 thru inter-agency collaboration and the study on the abuses against Children in Conflict with the Law (CICL).
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Offenders, Juvenile